The Documentation Center at the National University - Miranda Arguedas, Alice (1983)
The centers of Documentation are the managers of preserving and putting to the service, the set of documents elaborated with valuable scientific, literary, artistic, technological, philosophical character, etc.; in the different branches of the knowledge. These documents put to the service of the companies with readiness and efficiency, for the professionals who request them.